Respect in Kant’s Tugendlehre and its place in contemporary ethics - Darlei Dall'Agnol (Ethic@: an International Journal for Moral Philosophy)
The paper examines Kant’s conception of respect, especially in his work Metaphysical first principles of the doctrine of virtue (briefly Tugendlehre or Doctrine of Virtue), the second part of his The Metaphysics of Morals, and its place in contemporary ethics. The main question it asks is this: is respect just a feeling, a particular virtue or a moral duty/right? The initial hypothesis is that, in the relevant sense, respect is so to speak a “dutright,” that is, a duty that is at the same time a right. It leads to a fundamental principle, namely respect for persons, defining ‘person’ as a bearer of rights/obligations. Leaving Kant’s metaphysical commitments aside, it shows that this is one of the most important Kantian contributions to contemporary ethics